Monster hunting for beginners - Mark, Ian; Mark, Ian (London: Farshore, 2022)
Monster hunting isn't as easy as it looks. And Jack should know. Because an ogre has just appeared in his garden and tried to eat his aunt. (She was the winner of the World's Worst Aunt competition, but that's not the point). After (sort of accidentally) defeating the aunt-eating ogre, Jack finds himself apprenticed to a tiny, grumpy, 200-year-old monster hunter called Stoop and heading off to Cornwall, where more ogres are terrorising the town of King's Nooze. All he has are his wits, his catapult and a magical - sometimes unreliable - book called 'Monster Hunting for Beginners'. Not gonna lie, Jack's a bit worried he might not be the hero the residents of King's Nooze were waiting for. But then again, how many terrifying, bloodthirsty monsters can there really be out there?
Fiction 9+